Lightweight soundproofing meta-panel for separate wide frequency bands. (1st February 2023) - Kim, Jiwan; Choi, Eunji; Jeon, Wonju
Highlights: A lightweight soundproofing meta-panel that suppresses noise in separate wide frequency bands. A geometrical frame to isolate sound waves in separate bands based on a multi-scale concept. High sound transmission loss over a wide frequency range by inducing negative effective material properties of the meta-panel. Experimental evaluation of the insertion losses of the meta-panel aiming at practical application in electric cars. Abstract: We propose a lightweight soundproofing meta-panel that suppresses noise in separate wide frequency bands. The meta-panel has a multi-scale lattice structure sandwiched by two thin membranes. High sound isolation over a wide frequency range is achieved by inducing negative effective material properties of the meta-panel. Unlike a single-scale lattice structure, in which total transmission is unavoidable at certain frequencies due to resonances of the membranes, the meta-panel isolates sound waves effectively in separate wide bands with the aid of multiple reflections within the multi-scale lattice structure. A sound transmission loss exceeding 16.7 dB was realized within the range 100–1750 Hz by a meta-panel sample fabricated via three-dimensional printing. Aiming at practical applications in electric cars, we evaluated the insertion loss of the meta-panel in a box-shaped structure for dual-band noise which consists of road noise (100–400 Hz) and motor noise (1050–1350 Hz) recorded from an actual electric car. The proposed meta-panel had an overall sound pressure level reduction of about 19 dB for the given dual-band noise with a small areal density of 1.51 kg/m 2, which is 1/20 times lighter than a steel plate with an equivalent reduction level.